TRITIUM TRANSFER AND CONCENTRATIfON IN THE OCEAN - Eko Hidayanto (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Environmental transport models have been developed for evaluation of radiation doses from tritium released into the atmosphere. Recently, models contain not only inhalation and skin absorption as routes of tritium transfer from the atmosphere to humans, but also the ingestion pathway. Tritium releasing to the environment is contribute to added tritium concentration in the ocean. This paper describes the tritium transfer from the environment to the human body and the possible health effects if it is taken inside the body, the factors which influence the differences of tritium concentrations in the coastal seawater, and the formula of the tritium concentration balance in the ocean surface.